COUNSELING ON COMMUNICATION IN THE PERSPECTIVE OF THE QUR'AN AT PESANTREN SIROJUL HUDA BOGOR - Mukhlisin, Mukhlisin; Nurrahmaniah, Nurrahmaniah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The principle of communication actually has a strong scientific foundation, because it comes from the Qur'an. Through the Qur'an, humans are actually invited to communicate. Every human being needs to communicate with other people. In the Qur'an, at least six types of speech or speech styles (qaulan) are found which are categorized as rules, principles, or communication ethics, namely 1) qaulan balîghan; 2) qaulan maisûran; 3) qaulan karîman: 4) qaulan ma?rûfan; 5) qaulan layyinan; dan 6) qaulan sadîdan. This counseling aims to improve students' understanding of the principles of Communication in the Qur'an. The methods used are presentation, discussion, and evaluation through pre-test and post-test. The results of the activity showed an increase in participants' understanding of the principles of communication in the Qur'an.